2023
DOI: 10.1038/s41398-023-02446-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and behavioral symptoms in neurological disorders

Abstract: Glycosylation, the addition of glycans or carbohydrates to proteins, lipids, or other glycans, is a complex post-translational modification that plays a crucial role in cellular function. It is estimated that at least half of all mammalian proteins undergo glycosylation, underscoring its importance in the functioning of cells. This is reflected in the fact that a significant portion of the human genome, around 2%, is devoted to encoding enzymes involved in glycosylation. Changes in glycosylation have been link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 146 publications
(175 reference statements)
0
11
0
Order By: Relevance
“…32 Glycan is a key molecule involved in the modification of lipids, proteins and other glycans. 33 Glycosylated lipids are involved in cell adhesion and glycosylated proteins are major components of cell membrane proteins. 34 Our cell-type enrichment analysis results indicated that the main fraction of the differentially expressed proteins was derived from neuronal cells, suggesting that the pathway changes observed in CSF were predominantly from neuronal cells; further investigation is required to validate this.…”
Section: Discussionmentioning
confidence: 99%
“…32 Glycan is a key molecule involved in the modification of lipids, proteins and other glycans. 33 Glycosylated lipids are involved in cell adhesion and glycosylated proteins are major components of cell membrane proteins. 34 Our cell-type enrichment analysis results indicated that the main fraction of the differentially expressed proteins was derived from neuronal cells, suggesting that the pathway changes observed in CSF were predominantly from neuronal cells; further investigation is required to validate this.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than simply measuring changes in protein expression levels, recent studies have focused on mining changes in protein post-translational modifications, especially glycosylation . Subtle changes in protein glycosylation, which can be detected by state-of-the-art mass spectrometry (MS), are closely associated with the onset and progression of PD . It has been reported that the glycosylation of Tau is an early abnormality in AD, , which may promote the hyperphosphorylation of Tau, and identifying PD-associated protein glycosylation may be a means of early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…26 Subtle changes in protein glycosylation, which can be detected by state-of-the-art mass spectrometry (MS), are closely associated with the onset and progression of PD. 27 It has been reported that the glycosylation of Tau is an early abnormality in AD, 28,29 which may promote the hyperphosphorylation of Tau, and identifying PD-associated protein glycosylation may be a means of early diagnosis. Aberrant protein glycosylation is involved in the pathogenesis of PD, and many key proteins in PD are regulated by glycosylation, including α-synuclein (α-Syn), 30 microtubule-associated protein 6 (MAP6), 31 triggering receptor expressed on myeloid cells 2 (TREM2), 32 or dopamine transporter (DAT).…”
Section: ■ Introductionmentioning
confidence: 99%
“…All cells of each species studied exhibited a dense layer of glycans (sequences of carbohydrates), known as the “glycan coat”, which covers the surface of their cells in the form of glycoproteins, glycolipids, and proteoglycans. , This glycan coat plays a crucial role in cell recognition and communication with other cells and biomolecules. Unfortunately, certain pathogens, such as the HIV virus and SARS-CoV-2, exploit this glycan coat to invade cells and cause infection. Glycosylation, the process of attaching glycans to proteins, occurs in more than 50% of cellular proteins, akin to decorative “glycan trinkets”. , However, the glycoproteins’ trinket box can be infiltrated by aberrant glycans that exhibit minor differences. Decorating proteins with these aberrant glycans can lead to serious diseases, including cancers and neurological disorders. , It is precisely because of the immense biological significance of glycans that they are well-deserved to be recognized as one of the four essential organic building blocks found in all forms of life. , In view of this, many nations have launched significant scientific initiatives for glycomics research.…”
mentioning
confidence: 99%
“…Unfortunately, certain pathogens, such as the HIV virus and SARS-CoV-2, exploit this glycan coat to invade cells and cause infection. Glycosylation, the process of attaching glycans to proteins, occurs in more than 50% of cellular proteins, akin to decorative “glycan trinkets”. , However, the glycoproteins’ trinket box can be infiltrated by aberrant glycans that exhibit minor differences. Decorating proteins with these aberrant glycans can lead to serious diseases, including cancers and neurological disorders. , It is precisely because of the immense biological significance of glycans that they are well-deserved to be recognized as one of the four essential organic building blocks found in all forms of life. , In view of this, many nations have launched significant scientific initiatives for glycomics research. However, this field still faces huge challenges, primarily arising from the low abundance and extensive structural heterogeneity of glycans.…”
mentioning
confidence: 99%